2015
DOI: 10.1002/ijc.29529
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anthropometric measures as predictors of cancer incidence: A pooled collaborative analysis of 11 Australian cohorts

Abstract: Obesity is a risk factor for cancer. However, it is not known if general adiposity, as measured by body mass index (BMI) or central adiposity [e.g., waist circumference (WC)] have stronger associations with cancer, or which anthropometric measure best predicts cancer risk. We included 79,458 men and women from the Australian and New Zealand Diabetes and Cancer Collaboration with complete data on anthropometry [BMI, WC, Hip Circumference (HC), WHR, waist to height ratio (WtHR), A Body Shape Index (ABSI)], linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 35 publications
9
39
2
Order By: Relevance
“…In fact, among short postmenopausal women who became overweight or obese due to adult weight gain after age 18 years but prior to baseline, risk associated with gluteal adiposity was substantially greater than that due to abdominal adiposity. This finding is consistent with the recent report by Harding et al [18] suggesting that hip circumference may be a better predictor of postmenopausal breast cancer than waist circumference.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, among short postmenopausal women who became overweight or obese due to adult weight gain after age 18 years but prior to baseline, risk associated with gluteal adiposity was substantially greater than that due to abdominal adiposity. This finding is consistent with the recent report by Harding et al [18] suggesting that hip circumference may be a better predictor of postmenopausal breast cancer than waist circumference.…”
Section: Discussionsupporting
confidence: 93%
“…The positive association was stronger in European [46,79,97,145] and North American studies [41,56,76,82,94,98,101,136] than Australian and New Zealand studies (10 studies, 1 publication [135]) (p for meta-regression = 0.04) (Table S13); and was more evident among never or former users [41,56,79,82,130,136] than current or ever users [41,56,79,130,177] of postmenopausal hormones (p-values for meta-regression ≥ 0.06) ( Figs. 4 and S47-S48).…”
Section: Waist and Hip Circumferences And Waist-to-hip Ratio And Posmentioning
confidence: 85%
“…for meta-regression < 0.001). Asian studies[59, 86,112,158,174] showed an average stronger positive association than studies from Europe[46,47,49,63, 66, 72, 79, 88, 91, 96, 97,115,120,125,143,153,168,169,171,172], North America[44,51,56,57, 75, 80, 81, 98,100,101,136,152,159,167,171,178], and Australia and New Zealand[68,135] …”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] These studies have provided consistent evidence to support a role for excess adiposity, as defined by having a BMI >25.0 kg/m 2 (overweight/obesity), in the development of breast cancer among postmenopausal women. [3][4][5][6][7][8] As a measure of adiposity, BMI is limited, in that it does not truly reflect one's body fat distribution, 9 and, therefore, may not precisely estimate breast cancer risk among persons with excess adiposity. In an attempt to better capture the influence of body fat distribution on risk of breast cancer, several epidemiological studies have investigated the associations of waist circumference (WC) and waist-to-hip-ratio (WHR), 4,8,10,11 indicators of central adiposity, with risk of postmenopausal breast cancer.…”
Section: Introductionmentioning
confidence: 81%